Catalogus translationum et commentarium, Mediaeval and Renaissance Latin translations and commentarias, Volumen XII, Ovid, Metamorphoses. Greti Dinkova-Bruun, (Ed.) y Julia Haig Gaisser y James Hankins, (Eds asociados). Toronto, Pontifical Institute of Mediaeval Studies, 2022. 559 pp. ISBN 978-0-88844-952-8 - Duce Pastor, Elena (Antigüedad y Cristianismo, 2022)
.